F Formulasi Dan Evaluasi Sediaan Serum Gel Ekstrak Gliserin Bunga Asoka (Ixora coccinea L.) - Rianti, Nur Addina; Audina, Mia; Muzdalifah, Nur; Ramadhan, Novalina Rossa; Donaretsi, Olga Nathania; Laili, Rofiatul (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background:  The most common causes of skin dryness and redness are free radicals, pollution and ultraviolet rays. Cosmetics are epidermal treatments to nourish the body. One of the emerging cosmetics is a serum gel preparation that can maintain elasticity and moisturize the skin. While one of the plants has the potential to be used as a safe active ingredient in cosmetics, namely the asoka flower plant (Ixora coccinea L.) which is rich in phytochemical compounds, such as flavonoids, saponins, tannins, alkaloids, glycosides, terpenoids and carbohydrates, so it has very strong antioxidant activity. Objective:  To determine the appropriate formulation of asoka flower extract serum gel preparation and the effect of varying the concentration of asoka flower glycerin extract on the physical evaluation of serum gel preparation. Methods: This study used an experimental approach method with a true experimental design. The serum gel preparation was divided into 2 treatments with 15% and 30% concentration of active ingredients. The optimal formulation of the preparation is adjusted to the evaluation results and requirements set. Results:  Formula I met the organoleptical evaluation criteria, pH, flow type, and adhesion, but did not meet the specifications for viscosity and spreadability. While formula II meets the specifications of organoleptical test, pH, viscosity, flow type, adhesion, and spreadability. Conclusion:  From the evaluation conducted, it was found that the most optimal formula was formula II with 30% extract concentration.  Based on statistical tests using the Mann-Whitney Test, there is no effect on variations in the concentration of asoka flower extract.